Measurement of the inclusive t t ¯ $$ t\overline{t} $$ cross section in final states with at least one lepton and additional jets with 302 pb −1 of pp collisions at s $$ \sqrt{s} $$ = 5.02 TeV - The CMS collaboration; A. Hayrapetyan; A. Tumasyan; W. Adam; J. W. Andrejkovic; T. Bergauer; S. Chatterjee; K. Damanakis; M. Dragicevic; P. S. Hussain; M. Jeitler; N. Krammer; et al. (Journal of High Energy Physics)
Abstract A measurement of the top quark pair ( t t ¯ $$ t\overline{t} $$ ) production cross section in proton-proton collisions at a centre-of-mass energy of 5.02 TeV is presented. The data were collected at the LHC in autumn 2017, in dedicated runs with low-energy and low-intensity conditions with respect to the default configuration, and correspond to an integrated luminosity of 302 pb −1. The measurement is performed using events with one electron or muon, and multiple jets, at least one of them being identified as originating from a b quark (b tagged). Events are classified based on the number of all reconstructed jets and of b-tagged jets. Multivariate analysis techniques are used to enhance the separation between the signal and backgrounds. The measured cross section is 62.5 ± 1.6 stat − 2.5 + 2.6 syst ± 1.2 lumi $$ 62.5± 1.6{\left(stat\right)}_{-2.5}^{+2.6}\left(syst\right)± 1.2\left(lumi\right) $$ pb. A combination with the result in the dilepton channel based on the same data set yields a value of 62.3 ± 1.5 (stat) ± 2.4 (syst) ± 1.2 (lumi) pb, to be compared with the standard model prediction of 69.5 − 3.7 + 3.5 $$ {69.5}_{-3.7}^{+3.5} $$ pb at next-to-next-to-leading order in perturbative quantum chromodynamics.